2020
DOI: 10.1002/agj2.20278
|View full text |Cite
|
Sign up to set email alerts
|

Herbage responses and nitrogen agronomic efficiency of bahiagrass–legume mixtures

Abstract: Bahiagrass (Paspalum notatum Flüggé) is the most utilized forage in Florida and requires N fertilization to optimize production. Integrating legumes into bahiagrass pastures may reduce N fertilizer inputs and improve forage nutritive value. This 2-yr, 2-location, on-farm study established two legumes, alfalfa (Medicago sativa L.) or rhizoma peanut (RP; Arachis glabrata Benth.), in mixtures with bahiagrass. We compared bahiagrass-legume mixtures + 45 kg N ha −1 harvest −1 with their non-N fertilized monoculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Santos et al. (2020) reported similar results when alfalfa was growing in association with bahiagrass; nonetheless, the authors reported an even lesser contribution of alfalfa at the beginning of the growing season than that reported in this study. Alfalfa proportion in mixtures with temperate grasses can be as high as 77–99% during the establishment year and remain circa 50% after 3 yr (Aponte et al., 2019).…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Santos et al. (2020) reported similar results when alfalfa was growing in association with bahiagrass; nonetheless, the authors reported an even lesser contribution of alfalfa at the beginning of the growing season than that reported in this study. Alfalfa proportion in mixtures with temperate grasses can be as high as 77–99% during the establishment year and remain circa 50% after 3 yr (Aponte et al., 2019).…”
Section: Resultssupporting
confidence: 69%
“…In another study performed simultaneously in the same locations, with the same N regimes but utilizing bahiagrass instead of bermudagrass, Santos et al. (2020) reported that total HA of bahiagrass + 90 kg N ha −1 harvest −1 was not different from bahiagrass–alfalfa or bahiagrass–RP receiving 45 kg N ha −1 harvest −1 . Thus, bermudagrass (14,665 kg DM ha −1 yr −1 , on average) response to N fertilization in the present study was apparently greater than observed for bahiagrass (10,600 kg DM ha −1 yr −1 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations